Assessing the Neurotoxicological Effect of the Acute Paraquat Aerosols Exposure in Causing Parkinsonism on Mouse through Behavioral Assays - Sherlo Maulana; Santi Nurul Kamilah; Choirul Muslim; Aceng Ruyani; R. R. Sri Astuti (Universitas Airlangga, 2022)
Background: In the scientific community, there is no consensus that paraquat, a widely used herbicide, has a strong relationship with the occurrence of Parkinson's disease. A reliable epidemiological explanation of how paraquat can induce parkinsonism is urgently needed because it relates to the agriculture community's potential public health problem. Objective: In this study, mice exposed to aerosols of paraquat solution were assessed by behavioral assays designed to observe whether mice exposed to paraquat aerosols develop cardinal symptoms of Parkinson's disease, such as tremor-at-rest, bradykinesia, rigidity, and postural instability. Methods: To obtain the intended information, we carried out the observation on distal extremities, catalepsy test, wire suspension test, and swimming test consisting of the head position sub-test, the involvement of limbs sub-test, and the swimming direction test, respectively, to both the group of mice exposed to paraquat aerosols and the one which is not. Results: According to the result of the independent-samples t-test calculation on the data obtained from behavioral assays, a significant difference is shown only by the wire suspension test used to assess the development of forelimb rigidity and not the others. Conclusion: Therefore, this study showed that daily exposure for a week to paraquat aerosols insignificantly causes tremor-at-rest, bradykinesia, and postural instability in studied mice but dramatically affects their forelimb performance in the form of rigidity.